2021
DOI: 10.21608/evmspj.2021.142812
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular identification of Sarcocystis spp.infecting water buffaloes (Bubalus bubalus) in Sharkia Province, Egypt.

Abstract: Ras et al. INTRODUCTIONSarcocystis spp. is one of the most common protozoan foodborne parasites infecting both humans and many species of animals (Amairia et al., 2016). While, Sarcocystis spp. are intracellular cyst forming parasites, it requires two obligatory hosts; the asexual stages develop in an herbivorous intermediate host and the sexual stages develop only in carnivorous definitive hosts (Bucca et al., 2011; El-Dakhly et al., 2011). Hence, more than one Sarcocystis spp. can infect one host (Mekibib et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…Higher prevalence of 87% in India (35) and 94%, 85.96%, and 82.3% in Egypt (36, 16, 2) were detected. Older buffaloes had a significantly higher prevalence than younger ones similar to the previous reports in Vietnam (30) and Egypt (16,17). This may be due to prolonged exposure to infections (17).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Higher prevalence of 87% in India (35) and 94%, 85.96%, and 82.3% in Egypt (36, 16, 2) were detected. Older buffaloes had a significantly higher prevalence than younger ones similar to the previous reports in Vietnam (30) and Egypt (16,17). This may be due to prolonged exposure to infections (17).…”
Section: Discussionsupporting
confidence: 86%
“…Older buffaloes had a significantly higher prevalence than younger ones similar to the previous reports in Vietnam (30) and Egypt (16,17). This may be due to prolonged exposure to infections (17). Other authors reported a slight variation in prevalence in India (12) and Egypt (2).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations